SCALE OF TEACHER’S VALUATION I-S - Clemente Carrión, Antonio; Albiñana Hernández, Paz; Doménech Gregori, Francisca (Anales de Psicología / Annals of Psychology, 1999)
This study shows the effectiveness of the scale of Teacher’s Valuation. The teacher evaluates students intelligence and socialization. Results from factor analysis of 24 ítems resulted in three factors. These factors were Valuation of Intelligence, Valuation of Social Relationship and Valuation of Respect for Authority. Regression analyses showed that the factors of the Scale I-S were better in prediction of School Achievement than factors of Selfconcept, School Maladjustment and Personality. Samples were chosen from students of both sexes from first and second level of secondary school (aged 12-16 years old). The results of regression analyses showed the best predictors of School Achievement are the teacher’s valuations, especially, Valuation of Intelligence. This variable explains the most explains the most variance percentage in the regression analyses. Moreover, Valuation of Social Relationship and Valuation of Respect for Authority are important factors in order to explain the variance percentage.